2021
DOI: 10.3389/fphar.2021.664123
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Gold Nanorods in Photothermal Therapy: Recent Progress and Perspective

Abstract: Cancer is a life-threatening disease, and there is a significant need for novel technologies to treat cancer with an effective outcome and low toxicity. Photothermal therapy (PTT) is a noninvasive therapeutic tool that transports nanomaterials into tumors, absorbing light energy and converting it into heat, thus killing tumor cells. Gold nanorods (GNRs) have attracted widespread attention in recent years due to their unique optical and electronic properties and potential applications in biological imaging, mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 207 publications
(291 reference statements)
0
54
0
Order By: Relevance
“…Plasmon resonance can be changed by adjusting the length-to-width ratio or effective volume of the rod ( 18 ). Therefore, it can be absorbed by the tumor tissue due to the penetration effect while maintaining a small diameter and better light absorption properties to simultaneously achieve the effect of photothermal treatment ( 30 , 31 ). Furthermore, studies have shown that gold nanorods modified with low-density lipoprotein binding domain-binding polypeptide (RLT polypeptide) have a relatively evident inhibitory effect in the gastric cancer cell.…”
Section: Gnps With Different Structuresmentioning
confidence: 99%
“…Plasmon resonance can be changed by adjusting the length-to-width ratio or effective volume of the rod ( 18 ). Therefore, it can be absorbed by the tumor tissue due to the penetration effect while maintaining a small diameter and better light absorption properties to simultaneously achieve the effect of photothermal treatment ( 30 , 31 ). Furthermore, studies have shown that gold nanorods modified with low-density lipoprotein binding domain-binding polypeptide (RLT polypeptide) have a relatively evident inhibitory effect in the gastric cancer cell.…”
Section: Gnps With Different Structuresmentioning
confidence: 99%
“…AuNRs were incorporated into mesoporous silica [97,98], biodegradable polymeric matrix [99], and liposomes to facilitate the targeted release of ruthenium(II) polypyridyl complexes [100]. For more detailed information, the readers are referred to resent original papers [101][102][103][104][105][106][107][108][109] and related citations in recent reviews [77,[110][111][112][113][114][115].…”
Section: Au Nanorods (Aunrs)mentioning
confidence: 99%
“…Under high temperatures, normal cells can be in the heat stress state [182]. During this process, the expression of heat shock protein is upregulated, helping to reduce the damage caused by protein denaturation and inhibit the activation of apoptosis-related pathways [183]. PTT mediated by gold-based nanomaterials can induce physiological and biological changes in the surrounding tumor environment, which can maximize the cytotoxicity of PTT and improve the efficacy of secondary therapy.…”
Section: Cell Death Mechanism Induced By Pttmentioning
confidence: 99%